Impact of the Center of Excellence Vocational High School Program on the Interest of New Learners - Edhy Susatya; Adhy Kurnia Triatmaja; Eko Suratno; Fandi Faisyal Fachri (Journal of Vocational Education Studies, 2023)
The main problem of private schools is the difficulty of finding new learners (NL), exacerbated by the Covid-19 pandemic, making private schools even more slumped, including private Centers of Excellence Vocational High School (VHS CoE). Research objectives is to analyze; (1) promotion strategies for the private VHS CoE, (2) the impact of the VHS CoE on the interest of NL, and (3) the benefits of the VHS CoE. Qualitative descriptive research methods. The research sample was four private VHS CoE. Stages of research; (1) formulate problems, (2) determine the subject, (3) compile interview guidelines, (4) collect data, (5) sort and analyze data, (6) make conclusions. The results: (1) the private VHS CoE conduct direct socialization to pre-VHS, school residents, related institutions, and the community, and form a management team. Direct socialization is the most effective promotion strategy compared to other strategies, (2) the VHS CoE has an impact on NL interest fluctuatingly. The school program is the main consideration for NL to register at VHS CoE, while according to interests and talents is the main reason for NL to choose a flagship expertise program, and (3) the benefits of the VHS CoE, among others; improving the quality of schools, making it easier to get a job, and according to industry needs. The results of the study are expected to be the consideration of relevant agencies in making policies for the VHS CoE and for preparing strategies for capturing NL for private vocational schools.